Pharmacological Interactions of Nintedanib and Pirfenidone in Patients with Idiopathic Pulmonary Fibrosis in Times of COVID-19 Pandemic - José M. Serra López-Matencio; Manuel Gómez; Esther F. Vicente-Rabaneda; Miguel A. González-Gay; Julio Ancochea; Santos Castañeda (MDPI AG, 2021)
The discovery of antifibrotic agents have resulted in advances in the therapeutic management of idiopathic pulmonary fibrosis (IPF). Currently, nintedanib and pirfenidone have become the basis of IPF therapy based on the results of large randomized clinical trials showing their safety and efficacy in reducing disease advancement. However, the goal of completely halting disease progress has not been reached yet. Administering nintedanib with add-on pirfenidone is supposed to enhance the therapeutic benefit by simultaneously acting on two different pathogenic pathways. All this becomes more important in the context of the ongoing global pandemic of coronavirus disease 2019 (COVID-19) because of the fibrotic consequences following SARS-CoV-2 infection in some patients. However, little information is available about their drug-drug interaction, which is important mainly in polymedicated patients. The aim of this review is to describe the current management of progressive fibrosing interstitial lung diseases (PF-ILDs) in general and of IPF in particular, focusing on the pharmacokinetic drug-drug interactions between these two drugs and their relationship with other medications in patients with IPF.